PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI MIPA SMA NEGERI 1 PASAMAN - Doni Pratiwi (Jurnal Edukasi dan Penelitian Matematika, 2022)
Mathematics learning outcomes are benchmarks that can be used to see how far students understand in the concepts that being taught. But in reality, students of class XI MIPA SMAN 1 Pasaman have mathematics learning outcomes that have not been achieved optimally.  To fix that problem, the Think Pair Share (TPS) learning model can be applied. The research aims to determine whether students who learn with the TPS have better outcomes of mathematics learning than students who learn to use direct learning model and to describe how the development of mathematics learning outcomes of students who learn with the TPS learning model. This research is a combination of descriptive research and quasi-experimental research. The design of the research that used was a nonequivalent (posttest only) control group design. The results of this research are the experiment class and control class students  have an average of each  class 88.67 and 81.56. The conclusion of this research is that the experiment class had better learning outcomes than the control class. Its obstained based on the hypothesis test, with P-value 0,000. Keywords–Mathematics Learning Outcomes, Think Pair Share Learning Model, Quasi Experiment